RELATIONSHIP IN INFORMATION MEDIA AND DATING ACTIVITIES TO ADOLESCENT LEVELS OF KNOWLEDGE ABOUT PRE-MARITAL SEXUAL AT GEMA KARYA BAHANA SCHOOL, BEKASI CITY, 2022 - Titin, Titin; Manullang, Riyen Sari; Pangaribuan, Maslan; Izwardhy, Doddy; Purwanti, Emi; Santosa, Puji Raharja (STIKes Medistra Indonesia, 2025)
The main problems of adolescent reproductive health in Indonesia are the lack of provision of information regarding reproductive health, the problem of shifting adolescent sexual behavior, the lack of health services and unsupportive legislation.To determine the relationship between information media and dating activities on the level of knowledge of adolescents about premarital sex at Gema Karya Bahana Vocational School, Bekasi City in 2022. Using a cross-sectional research design. The number of samples in this study amounted to 70 respondents. The inclusion criteria of this study were students who were willing to become respondents in class 11 at Gema Karya Bahana Vocational School, Bekasi City, students who had never previously received counseling on premarital sexual and reproductive health and were not married. The results of the statistical test found that there was a relationship between information media and the level of knowledge of adolescents about premarital sex (p=0.002) and there was a relationship between dating activities and the level of knowledge of adolescents about premarital sex (0.024). From the research results, it is proven that there is a relationship between information media and the level of knowledge of teenagers about premarital sex and there is a relationship between dating activities and the level of knowledge of teenagers about premarital sexuality. It is hoped that schools can provide more education regarding sexuality issues in relationships inside and outside school.